O haniebnej śmierci Ariusza - Niewiadomska, Magdalena (Warszawskie Studia Teologiczne, 2020)
The oldest description of Arius’s death can be found in two letters of Athanasius of Alexandria which both were written 20 years after that event. Athanasiuspresented the circumstances of heresiarch’s death and gave them particular moraldimension. Many of futher Christian sources iterated actually the elements presented by Athanasius: the parallel with death of Judas Iscariot, the indication of God’s intervention at the moment of the return of Arius to the church’s community. Notwithstanding they added some drastic descriptions regarding physiology which created the power of expression. The absence of Arian sources makes comparative analysis impossible. In the description of Arius’s death there are the elements typical for the death of a persecutor of Christians. They can be seen from otherdescriptions where there are some common elements: the celerity and pain of death and many disgusting details. They indicate not only the typical character of such a description but also impose moral judgment on readers.